The Effects of Various Restorative Techniques on the Fracture Resistance of Pulpotomized Permanent Premolars - Yasamin Ghahramani; Fereshteh Shafiei; Zahra Jowkar; Sepideh Kazemian (International Journal of Dentistry)
Aim. This study aimed to evaluate the effects of various restorative techniques on the fracture resistance of pulpotomized premolars with mesioocclusodistal (MOD) cavities treated with mineral trioxide aggregate (MTA) or calcium enriched mixture (CEM) cement. Materials and Methods. One hundred and eight sound extracted maxillary premolars were randomly assigned to nine experimental groups (n = 12). The teeth in group 1 did not receive any preparation. Class II MOD cavities were prepared in the other experimental groups. In groups 2, 4, 6, and 8, tooth-colored MTA was used for pulpotomy. In groups 3, 5, 7, and 9, CEM cement was used for pulpotomy. Groups 2 and 3 were left unrestored. Groups 4 and 5 were restored with amalgam. Groups 6 and 7 were restored with a conventional composite resin, and groups 8 and 9 were restored with bulk-fill giomers. Fracture resistance was measured, the fracture pattern of each specimen was assessed, and the results were statistically analyzed. Results. The fracture resistance of group 1 was significantly higher than those of the other groups (p<0.05). The fracture resistance of group 2 (MTA + amalgam) was statistically lower than those of all experimental groups (p values < 0.05) except groups 3, 4, and 5 (p values > 0.05). No statistically significant differences were found between the groups restored with amalgam, conventional composite resin, and bulk-fill giomer (groups 4, 5, 6, 7, 8, and 9) (p values < 0.05). The highest rate of mode 1 fracture (restorable fracture) was observed in group 1 followed by groups 8 and 9. Conclusion. No significant differences were found among the fracture resistances of the restored teeth using various restorative techniques. Bulk-fill giomers followed by conventional composite resin were better able to prevent unfavorable fractures compared to amalgam. Therefore, they seem to be more reliable for the restoration of pulpotomized teeth with MOD cavities.